2022
DOI: 10.3126/banko.v32i2.50892
|View full text |Cite
|
Sign up to set email alerts
|

Distribution pattern of corticolous lichens in different areas of Kathmandu valley, Nepal

Abstract: This study attempts to document the lichen species and their distribution in different areas of Kathmandu valley, Nepal. Twenty sampling sites with different degrees of air pollution categorized as disturbed (industrial, heavy traffic and residential areas) and undisturbed areas (clean area) were selected for the study. Sampling was done using the quadrat method. To enumerate the total number of lichen species found in Kathmandu valley, lichen specimens were collected from inside as well as outside the quadrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Similarly, Magar et al( 2019) studied the microbiological contaminants of drinking water in different samples of Kathmandu Valley. The result revealed that coliforms were present in both groundwater and bottled water samples Karmacharya (2021) investigated processed water quality from the different treatment plants in Kathmandu Valley. Sarkar et al (2022) also analyzed drinking water samples from Kathmandu Valley, and the result showed that water samples contained widespread bacterial contaminations and arsenic, iron, manganese, and aluminum.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Magar et al( 2019) studied the microbiological contaminants of drinking water in different samples of Kathmandu Valley. The result revealed that coliforms were present in both groundwater and bottled water samples Karmacharya (2021) investigated processed water quality from the different treatment plants in Kathmandu Valley. Sarkar et al (2022) also analyzed drinking water samples from Kathmandu Valley, and the result showed that water samples contained widespread bacterial contaminations and arsenic, iron, manganese, and aluminum.…”
Section: Literature Reviewmentioning
confidence: 99%